Recovery of Potassium from Incineration Ash of Chicken Dropping (IACD) by Sulphuric Acid Leaching Followed by Adsorption Using Orange Waste Gel - Paudyal, Hari; Inoue, Katsutoshi; Pangeni, Bimala (Journal of Nepal Chemical Society, 2021)
Two types of leaching solution namely; aqua-regia and 1MH2SO4 were investigated for the leaching of K(I) from incineration ash of chicken dropping (IACD), in this study. SOJR and Na(I)-SOJR adsorbents were prepared from orange juice residue for the adsorption of K(I) from IACD leached liquor, which was compared with READF-(PG) and 200CT resin. The characterization of IACD leaching was done in EDX and FTIR spectroscopic techniques. Aqua-regia solution completely dissolved IACD and all the adsorbents. One molar sulphuric acid (1MH2SO4) solution was optimized for effective leaching of K(I) from the IACD sample. SOJR, Na(I)-SOJR, and 200CT adsorbed K(I) from leached liquor whereas K(I) was insignificantly adsorbed onto READF-(PG). The desorption of adsorbed K(I) could be successfully done by H2SO4 solution for recovery and adsorbent regeneration for further usage. From comparisons, Na(I)-SOJR investigated in this study was found to be equally effective with a commercially available cation exchanger (200CT resin). Therefore, a new method of H2SO4 leaching of IACD followed by adsorption using Na(I)-SOJR investigated in this work can be an economic, environmentally benign, and promising technique for the recovery of K(I) ion from leach liquor of IACD.